The Influence of Islamic Corporate Governance and Islamic Corporate Social Responsibility on Reputation with Company Performance as a Variable Moderating (at Commercial Banks Sharia 2017-2021) - Nastiti .; Maryam Batubara; Wahyu Syarvina (LPPM UIKA Bogor, 2023)
This study aims to determine the effect of Islamic corporate governance and Islamic corporate social responsibility on reputation with performance as a moderating variable. This research is qualitative research with secondary data. The object of this research is Islamic Commercial Banks, taking samples using a purposive sampling method. The data used are from 8 Islamic Commercial Banks within 5 years obtained from the annual report documentation published through the bank's official website. The data were analyzed using the panel data regression method using the e-views analysis tool 12. The results showed that the ICG variable had a significant effect on BUS's reputation. ICSR has no significant effect on BUS's reputation. ROE is unable to moderate the ICG relationship to BUS's reputation. Likewise, ROE is unable to moderate the relationship between ICSR and BUS reputation.